On Kenmotsu Manifolds Satisfying Certain Curvature Conditions - Shah, Riddhi Jung (Journal of Institute of Science and Technology, 2018)
Available with full text. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 56-62